2019
DOI: 10.29333/ejmste/109607
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Learning Effect of Advanced Mathematics among Chinese College Students in Social Science Majors

Abstract: The learning effect of advanced mathematics among Chinese college students in social science majors is affected by factors such as personal factors, teachers' affective support, teaching methods, and environment factors. The aim of this study was to explore the interrelationships between these factors and learning effects on Advanced Mathematics. This study also helps to further describe how to solve these influencing factors, making it more valuable and applicable. The research samples comprised 413 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…CB-SEM Statistical Applications [84,90,99,111] Lisrel (N = 4 studies) [80][81][82][83][91][92][93]97,109,117,119] Amos (N = 11 studies) [94,98,100,[106][107][108]112] Mplus (N = 7 studies)…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…CB-SEM Statistical Applications [84,90,99,111] Lisrel (N = 4 studies) [80][81][82][83][91][92][93]97,109,117,119] Amos (N = 11 studies) [94,98,100,[106][107][108]112] Mplus (N = 7 studies)…”
Section: Studymentioning
confidence: 99%
“…By utilizing the other version of Amos, which is v.22, the results from [109] reflect how TAM constructs significantly influence the acceptance of e-books among mathematics and statistics students at universities. A discussion in [119] was related to the interrelationships between these factors and the learning effects on advanced mathematics. The result of the study revealed that the affective support of teachers is positively correlated with students' learning cognition and learning self-efficacy.…”
Section: Studymentioning
confidence: 99%
“…Rendahnya hasil belajar analisis kompleks dapat disebabkan oleh berbagai macam faktor. Faktor eksternal seperti lingkungan belajar yang meliputi kurikulum, dukungan guru, pendampingan orang tua, dukungan sarana, dan lain-lain dapat mempengaruhi hasil belajar (Xiang et al, 2019). Di samping itu, faktor internal seperti sikap terhadap (Xiang et al, 2019), kecemasan matematika (Udil et al, 2017;Udil & Israfil, 2022), persepsi (Mutodi & Ngirande, 2014), gaya kognitif (Kiarsi & Ebrahimi, 2021), motivasi (Helma & Murni, 2020), dan sebagainya juga dapat mempengaruhi hasil belajar matematika peserta didik.…”
Section: Gambar 1 Rata-rata Hasil Belajar Analisis Kompleksunclassified
“…Mathematics studies in universities play an increasingly important role not only in engineering, but also in social science education, such as in such interdisciplinary fields as mathematical linguistics, quantitative sociology, etc. (Xiang, Wan, & Zhou, 2019). At the same time, it is no secret that mathematics studies are becoming more and more difficult both in secondary schools and universities.…”
Section: Introductionmentioning
confidence: 99%